P049 COMPARISON OF USTEKINUMAB CONCENTRATION ASSAYS AND ANTIBODIES-TO-USTEKINUMAB ASSAYS. (7th February 2019) - Marini, Joseph C; Chun, Kelly Y; Rebarchak, Shannon; Dogmanits, Shannon; Sloan, Sheldon; Shankar, Gopi
Abstract: Background: Monitoring ustekinumab (UST) concentrations and antibodies-to ustekinumab (ATU) during IBD treatment may allow more informed decisions in assessing exposure/response and appropriate dosing. To aid in interpreting results in the context of Janssen's published UST results, the reliability of different assays measuring UST and ATU were compared with those from Janssen. This abstract reports the comparison of the UST and ATU assays from Laboratory Corporation of America (LabCorp, Calabasas, CA, USA) and Janssen (JRD, Spring House, PA, USA). Results from the other companies will be reported at a later time. Methods: Blinded test samples, prepared by JRD, were sent to the LabCorp and JRD labs for UST and ATU assessments. Results were reported to JRD for integrated analyses. All assays were tested for specificity, selectivity, accuracy and precision. ATU assays were evaluated for sensitivity, drug interference, and potential interference of IL-12. UST and ATU were tested at LabCorp using Meso Scale Discovery (MSD®, Rockville, MD, USA) electrochemiluminescent immunoassays (ECLIA) and at JRD using different MSD ECLIAs. The lower limit of quantification was 0.4 mg/mL for the LabCorp UST concentration assay and 0.1688 mg/mL for the JRD UST concentration assay. Results: Strong agreement was observed between the JRD and LabCorp UST assays. Specificity was demonstrated when both UST assays accurately detected 1.0 or 10.0 mg/mL of UST but did not detect other human monoclonal antibodies (mAb). The presence of ATU titers up to 200 or IL-12 concentrations up to 100 pg/mL did not interfere with the UST assessment in either assay. Accuracy was confirmed by 3 independent measurements of UST-spiked (0.06-32 mg/mL) human psoriasis (PSO) sera. However, accuracy was not confirmed when testing incurred samples from PSO subjects previously exposed to ustekinumab at concentrations below approximately 1.3 mg/mL. Both UST assays were precise, as determined by inter-occasion reproducibility. Strong agreement was observed between the JRD and LabCorp ATU assays. Both ATU assays specifically detected anti-UST antibodies; results were not affected by high titer antibodies against other human mAb. Both ATU assays demonstrated drug tolerance to 8.0 mg/mL of UST, with the LabCorp assay demonstrating drug tolerance to 32.0 mg/mL. Concentrations of free or bound IL-12 (≤100 pg/mL) did not interfere with ATU detection in either assay. Both ATU assays were reproducible. Conclusion: Our study results indicate that the LabCorp UST concentration and ATU assays strongly correlate with those from JRD. The substantial agreement between the LabCorp and JRD assays may provide support to clinicians in their use of these assays, and for understanding their patients' UST and ATU results relative to published data from clinical studies of UST.